EFEKTIFITAS LAYANAN INFORMASI UNTUK MENINGKATKAN SIKAP SISWA DALAM BERKOMUNIKASI DENGAN GURU DI SMA YASMIDA AMBARAWA - Safwan Adiputra (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The research is based on the problem of the lack of student attitudes in communicating with teachers. The research problem is the attitude of students is not good. Which is formulated as follows: (1) Is there an increase in the effectiveness of student attitudes in communicating with teachers after layanaan information given in SMA Yasmida Ambarawa?This study aims to determine the effectiveness of information services to the improvement of student attitudes in communicating with teachers in class XI SMA Yasmida Ambarawa. The population in this study is a class XI student who numbered 118, the samples taken were 40 students is class XI and XI IPA1 IPS1, and the method used is quantitative experiments and techniques of data collection is questionnaire. Services are conducted twice a meeting that is gathering information services carry out pretest and posttest. From the results of the implementation is done, there was an increase. Which is quite large, especially the second meeting of the findings on the results of the posttest. To test the hypothesis used by the formula Wilcoxon signed rank test using SPSS for windows version 20:00 Wilcoxon test used to analyze the results - observations from two different whether or not the data.Based on research conducted at SMAN Yasmida Ambarawa on students 'attitudes can be summed up results of the analysis of the increase in the students' attitude with kolmogrov simirnov 2 independent of the control group 101.2000. and experiment 120.1000. Daris results conducted an increase that is better than ever.Suggested for a tutor should be more active, creative so that students are more enthusiastic in the implementation of information services better and more improved again, for the next researcher, is expected to help research on improving the attitude is not good to be good and very good